Product barcode and expiry date detection for the visually impaired using a Smartphone - Peng, En; Li, Ling; Peursum, Patrick (IEEE, 2012)
The International Conference on Digital Image Computing: Techniques and Applications (DICTA) is the premier conference of the Australian Pattern Recognition Society (APRS). It is the main Australian conference on computer vision, image processing, pattern recognition, and related areas. DICTA was established as a biannual conference in 1991 and became an annual event in 2007. Although, DICTA is organized within Australia every year, it attracts a large number of international authors and delegates. DICTA features distinguished keynote speakers from around the world. DICTA 2012 is the fourteenth conference in its series and maintains the high international standards of cutting edge computer vision research. This year, DICTA allowed the submission of up to 8 page papers to accommodate more detailed theory and analysis. Each paper submitted to DICTA 2012 was reviewed by at least two independent reviewers from the technical program committee and external reviewers using a double blind system. The total number of papers submitted to DICTA 2012 was 172. Out of these, the committee accepted 79 papers which equals an acceptance rate of 45.9%. The organising committee then selected 39 papers for oral and 40 for poster presentation.